Dynamics of marketing automation adoption for organisational marketing process transformation: The case of Microsoft - Hong, Sung Hak; Park, Min Jae (International Journal of Electronic Customer Relationship Management, 2020)
As markets and customers rapidly digitalise with technological advances, companies are responding by increasingly introducing marketing automation (MA). This study aims to support successful MA adoption and marketing transformation. To achieve this aim, we design an MA adoption model based on Kotter's eight-step model, and we study the dynamics of the MA adoption process by analysing Microsoft's MA adoption case. Based on the results of the analysis, we present an MA adoption model in eight stages. The MA adoption model proposes a step-by-step transformation in adopting MA and suggests that to ensure successful completion, MA should be adopted in conjunction with marketing transformation rather than remaining on the level of technology adoption. The MA adoption model presented in this study is expected to help managers understand the dynamics of MA adoption and, thus, help them to build an appropriate MA adoption strategy.
Keywords: Case; Kotter's model; Marketing automation; Microsoft; Process transformation